Loneliness and Psychological Well-Being in Early Adulthood - Muhamad Nanang Suprayogi; Luthfi Nisrina Hamidah (Engineering Proceedings, 2024)
We examined the relationship between loneliness and psychological well-being in early adulthood in Jakarta, Indonesia. Using a quantitative method and the UCLA loneliness scale with 212 participants in early adulthood in Jakarta, Indonesia, we measured psychological well-being and loneliness. Ryff’s Scale of Psychological Well-Being was also used. A measuring scale was re-formulated in the Indonesian language. Loneliness and psychological well-being were negatively correlated (r = −0.692, p < 0.05). This result can be used to increase psychological well-being in early adulthood and maximize their productivity.